Commentary: Functional Neuronal CB2 Cannabinoid Receptors in the CNS - Onaivi, E.S (Bentham Science Publishers Ltd, 2011)
Cannabinoids are the constituents of the marijuana plant (Cannabis sativa). There are numerous cannabinoids and other natural compounds that have been reported in the cannabis plant. The recent progress in marijuana-cannabinoid research include the discovery of an endocannabinoid system with specific genes coding for cannabinoid receptors (CBRs) that are activated by smoking marijuana, and that the human body and brain makes its own marijuana-like substances called endocannabinoids that also activate CBRs. This new knowledge and progress about cannabinoids and endocannabinoids indicate that a balanced level of endocannabinoids is important for pregnancy and that the breast milk in animals and humans has endocannabinoids for the growth and development of the new born. There are two well characterized cannabinoid receptors termed CB1-Rs and CB2-Rs and these CBRs are perhaps the most abundant G-protein coupled receptors that are expressed at high levels in many regions of the mammalian brain. The expression of CB1-Rs in the brain and periphery and the identification of CB2-Rs in immune cells and during inflammation has been extensively studied and characterized. However, the expression of functional neuronal CB2-Rs in the CNS has been much less well established and characterized in comparison to the expression of abundant brain CB1-Rs and functional neuronal CB2-Rs has ignited debate and controversy. While the issue of the specificity of CB2-R antibodies remains, many recent studies have reported the discovery and functional characterization of functional neuronal CB2-Rs in the CNS beyond neuro-immuno cannabinoid activity.